2009
DOI: 10.3928/1081597x-20090813-07
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimicrobial Efficacy of Riboflavin and Ultraviolet Light on Staphylococcus aureus , Methicillin-resistant Staphylococcus aureus , and Pseudomonas aeruginosa

Abstract: Riboflavin in combination with UV light is an effective modality to eradicate the bacteria S aureus, MRSA, and P aeruginosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 20 publications
3
62
1
3
Order By: Relevance
“…The proteolytic enzymatic activity is the cause of clinical corneal melting during and following corneal infections. In vitro studies have demonstrated a good bactericidal effect of combined riboflavin and UVA on several bacterial species which are known pathogens in bacterial keratitis [159,160]. The effects on fungal and acanthamoebic activity in vitro were less favorable, showing no significant effect on viability [161,162].…”
Section: Other Indications For Riboflavin-uvx Collagen CXLmentioning
confidence: 99%
“…The proteolytic enzymatic activity is the cause of clinical corneal melting during and following corneal infections. In vitro studies have demonstrated a good bactericidal effect of combined riboflavin and UVA on several bacterial species which are known pathogens in bacterial keratitis [159,160]. The effects on fungal and acanthamoebic activity in vitro were less favorable, showing no significant effect on viability [161,162].…”
Section: Other Indications For Riboflavin-uvx Collagen CXLmentioning
confidence: 99%
“…In another in vitro study performed by Schrier A et al, the antibacterial action of riboflavin alone, UV light alone and the combination of riboflavin and UV light has been assessed on S. aureus, MRSA and P. aeruginosa. According to their results, no bacterial death was seen in plates of riboflavin alone and all S. aureus and MRSA plates exposed to UV light alone; however, significant bacterial death was observed in all plates exposed to the combination of riboflavin and UV light [19].…”
Section: Discussionmentioning
confidence: 99%
“…Антибактериальный эффект взаимодействия УФА и рибофлавина был доказан двумя независи-мыми друг от друга группами исследователей на культуре бактерий, выращенных на агаровой среде в чашках Петри [19,20]. Кроме того, в ходе этого ис-следования ряд бактериальных штаммов, относя-щихся к обычным возбудителям микробного кера-тита, был уничтожен при облучении рибофлавина ультрафиолетом.…”
Section: кросслинкингunclassified
“…[19] и группы A. Schrier и соавт. [20] стали появляться работы о применении метода КРЛ в лечении тяжелых бакте-риальных кератитов, включая бактериальные кера-титы с изъязвлением, грибковые и акантамебные кератиты [25][26][27][28][29][30].…”
Section: кросслинкингunclassified